Glenn-Colusa Irrigation District water balance model: a foundational component of a district resource management plan - Bettner, Thaddeus, author; Davids, Grant, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2010)
Glenn-Colusa Irrigation District (GCID) is in the process of developing a Resources Plan (Plan) to establish improved policies and decision making processes to better and more actively manage its available water supplies. The first element of the Plan will address Water Supplies and Transfers; it will be developed through evaluation of the district's recent historical and future water demands relative to available surface water and groundwater supplies. The analyses will reveal the probabilities, magnitudes and durations of possible future water supply shortage and surplus conditions. When combined with supporting legal and institutional review, the analyses will provide a basis for managing available water surface and groundwater supplies, shaping conjunctive water management policy, and evaluating potential surface water transfers. GCID is developing a water balance model, including related refinements to the District's water measurement, data management and reporting systems, to analyze historical and possible future water supplies and demands. The water balance will be calculated on a monthly time step for up to ten consecutive years, including winter months when rainfall is appreciable and irrigation demands are generally low. Individual water balances will be prepared for each of GCID's ten water operator areas, which can be combined to form the balance for the overall District. This paper provides a background description of GCID and discusses ongoing development of the water balance model and related improvements to GCID's flow measurement and data management procedures.
USCID water management conference
Presented at Upgrading technology and infrastructure in a finance-challenged economy: a USCID water management conference held on March 23-26, 2010 in Sacramento, California.